(untitled) (Conference Zone, 2022)
this state tells how, with the help of electronic textbooks, each student can use his knowledge at any time and in any place, or watch video lessons. Information technologies are widely implemented in the educational process, as well as in all spheres of life. The introduction of information technology in the educational process allows the use of new innovative tools. New to the collection, processing, analysis, storage, dissemination and use of information about various objects, objects and events, it will not be an exaggeration to say that electronic resources and electronic textbooks,which become an integral part of our modern society as a modern method and mechanism, provide us with comprehensive convenience and a wide range of opportunities. In the process of creating an electronic textbook, psychological, pedagogical, technical, technological, and aesthetic requirements are set. These requirements ensure the quality and perfection of electronic textbooks. It must meet the didactic requirements of traditional textbooks, such as electronic textbooks, textbooks and manuals